2013
DOI: 10.1016/j.jnoncrysol.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ge-doped optical fibre as a TL-mode detector

Abstract: This study analyses the thermally stimulated luminescence or thermoluminescence (TL) glow curve between 300 and 773 K of germanium-doped silica optical fibre. A main glow peak at 530 K with a characteristic spectral emission centred at 400 nm is found. Both features are particularly suitable for dosimetry.Thus, an investigation by the TL technique of some first clinically relevant features of a TL sensor like the doseand dose rate-responses is examined. The presented studies show that germanium doped silica fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This is e.g. the case in germanium-doped fibers, where recombination mainly takes place on germanium-related oxygen deficient centers [9], or in ytterbium-doped fibers where ytterbium ions were shown to be the largely predominant RCs [8]. Then, color centers are essentially related to the trapping of carriers whose polarity is opposite to the charge of RCs.…”
Section: The Model and Its Global Treatmentmentioning
confidence: 99%
“…This is e.g. the case in germanium-doped fibers, where recombination mainly takes place on germanium-related oxygen deficient centers [9], or in ytterbium-doped fibers where ytterbium ions were shown to be the largely predominant RCs [8]. Then, color centers are essentially related to the trapping of carriers whose polarity is opposite to the charge of RCs.…”
Section: The Model and Its Global Treatmentmentioning
confidence: 99%
“…Researchers from LPMC 14 recently explored the TL properties of Ge-doped fibers previously stripped of their polymer sheath (caution related to the fiber heating) and then irradiated with X-rays [52]. It has been shown that such type of fiber, used itself as a dosimeter, fulfills the TL characteristics required by medical dosimetry, such as high sensitivity and dynamic range, and low dependency on the dose rate.…”
Section: Thermoluminescent Dosimetrymentioning
confidence: 99%
“…The laser stimulation of the OSLD is triggered through the fiber at the end of irradiation, and the luminescent signal is immediately transmitted via the fiber to the PMT [54][55][56][57]. The OSL emission following a stimulation pulse is very fast, and then Comparison of the glow curves of GeD2 fiber, TLD-700 and TLD-500 irradiated and read out in the same experimental conditions [52]. Fig.…”
Section: Optically Stimulated Luminescent Dosimetrymentioning
confidence: 99%
“…In attempts to improve the TL response of SiO 2 , investigations have been performed using different phosphor additives and extrinsic dopants in glass and optical fibers, the dopants including aluminum [6], germanium [4,[6][7][8], lithium and barium [9], zirconium oxide (ZrO 2 ) [10], copper activated calcium borate (CaB 4 O 7 :Cu) nanocrystals [11], manganese doped calcium tetraborate (CaB 4 O 7 :Mn) nanocrystal [12], lithium potassium borate glass doped with titanium oxide (TiO 2 ) and magnesium oxide (MgO) [13], di-potassium yttrium fluoride (K 2 YF 5 ) crystals doped with samarium (Sm 3 þ ) and terbium (Tb 3 þ ) ions [14].…”
Section: Introductionmentioning
confidence: 99%